Optimization Of Food Product Sales System and Customer Service Through Customer Relationship Management Approach - Anggun Fergina; Yulva Cintakandida; Gina Purnama Insany (bit-Tech, 2025)
ABC Kitchen, a micro, small, and medium enterprise (MSME) in the culinary sector, faced operational inefficiencies due to manual data management and a lack of integration between ordering and payment processes. This study developed a web-based Customer Relationship Management (CRM) system using the IDIC (Identify, Differentiate, Interact, Customize) model to address these issues. Functional validation was conducted using black-box testing, which evaluates system performance against predetermined requirements without examining the internal code structure. Test results on four captured pages demonstrated a 100% success rate across 13 functional scenarios. The system enables automatic customer identification from transaction history, personalized promotions through preference-based differentiation, real-time interactions through an intuitive user interface, and service customization such as vouchers, various payment options, and VIP membership features. Furthermore, an analytics dashboard provides administrators with actionable insights to monitor customer behavior and sales trends, supporting data-driven decision-making. This study contributes to the MSME digital transformation literature by demonstrating how CRM integration can enhance customer engagement, improve operational efficiency, and provide a competitive advantage in a dynamic market environment. The novelty of this study lies in tailoring CRM to the specific operational and marketing needs of micro-scale culinary businesses, enabling sales growth and customer loyalty through an easily accessible sales system. This study demonstrates how context-specific digital CRM solutions can accelerate MSMEs' digital transformation, increase competitiveness, and create a sustainable foundation for growth in a dynamic market.